PENGARUH SERVANT LEADERSHIP, ORGANIZATIONAL CULTURE TERHADAP EMPLOYEE PERFORMANCE DIMEDIASI ORGANIZATIONAL COMMITMENT PADA PT XYZ - Edri, Rendi Fajar Utama; Sudaryanto, Sudaryanto; Panggalih, Barleyan Simon Tatag; Setyaningrum, Retno Purwani (JUDICIOUS, 2024)
High employee performance not only contributes directly to the achievement of organizational goals, but also plays a role in increasing customer satisfaction and company reputation. This research was conducted to determine the impact of Servant Leadership and Organizational Culture on Employee Performance mediated by Organizational Commitment at PT XYZ. This type of research is quantitative research, sampling is carried out by distributing questionnaires with a total sample of 50 respondents. The analysis technique used in this study is multiple linear analysis techniques using smartPLS version 3.0. Based on the findings of this study Servant Leadership does not have a positive impact on Employee Performance, Organizational Culture does not have a positive impact on Employee Performance, Servant Leadership does not have an impact on Employee Performance after being mediated by Organizational Commitment, Organizational Culture has an impact on Employee Performance after being mediated by Organizational Commitment, Organizational Commitment has a positive impact on Employee Performance.